Fusarium mycotoxins and human health. Review. - Shephard, Gordon S. (Plant Breeding and Seed Science, 2011)
Species within the genus Fusarium produce a diverse range of mycotoxins, many of which have signifi- cant impacts on human health. Of the five generally recognised major mycotoxins, three (fumonisins, de- oxynivalenol (DON) and zearalenone (ZON)) are produced by Fusaria. Apart from DON, other trichothecenes such as T-2 toxin, have received considerable international attention due to their impact on human health. The fumonisins, which occur ubiquitously in maize and its products, have been linked to oesophageal cancer, liver cancer and neural tube defects. DON, a frequent contaminant of maize, wheat and their products, although showing no carcinogenic potential, is immunomodulatory and produces emesis and growth retardation in animals. ZON is a naturally occurring endocrine disrupting chemical. Acute exposure to these mycotoxins has in each case been linked to outbreaks of human disease – gastro-intestinal effects in the case of fumonisins and DON, and precocious pubertal changes in the case of ZON. Concern over their toxicological effects has led to risk assessments by the Joint FAO/WHO Expert Committee on Food Additives (JECFA), which has set maximum tolerable daily intakes (TDI) of 2 µg/ kg body weight (bw) for fumonisins and 0.5 µg/kg bw for ZON. The initial TDI set for DON, namely 1 µg/kg bw has recently been updated by JECFA to include both 3- and 15-acetylDON. Apart from the above mycotoxins, a number of other secondary metabolites (moniliformin, beauvericin and fusaproliferin) are produced by different Fusaria and their effects on human health, either alone or in combination with other mycotoxins, is largely unexplored.